MANAJEMEN PAKAN PADA PEMBESARAN UDANG VANAME (Litopenaeus vannamei) DENGAN TEKNIK BLIND FEEDING DAN AUTOMATIC FEEDER FEED - Astuti, Santika Dewi; Waluyo, Waluyo; Tartila, Shobrina Silmi Qori; Romadlon, Akhmad; Samuki, Khairul (Universitas Teuku Umar, 2023)
Vaname shrimp is a fishery commodity with high economic value and a large export contribution. The maintenance period is long enough to make production results need to be considered directly. Feed as an important component that can affect growth, water quality, and production costs needs to be considered properly. The feed management program using blind feeding techniques has shown a significant impact on shrimp growth. The water quality factor does not have such a significant effect, except for ammonia which has increased due to the increase in the mortality rate of diseased shrimp. Water quality management with a blind feeding technique can be controlled with feed tests. The results of this observation were obtained directly from observation and active participation during the implementation of the street vendors.